OPTIMIZING DIGITAL MARKETING FOR MSMEs THROUGH CREATIVE DESIGN AND VISUAL BRANDING OF PALIMA FOODS - Ditiya Himawati; Sri Riswanti; Rehulina Apriyanti; Rooswhan Budhi Utomo; Sri Kurniasih Agustin; Ayu Akmaliyah; Nadila Putri Budi (Jurnal Ilmiah Ekonomi Bisnis, 2025)
The digital transformation of the marketing landscape presents significant opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs) seeking to expand reach and enhance competitiveness. This literature-based research analyzes the integration of creative design and visual branding as an innovative digital marketing strategy, assessing its impact on increasing brand awareness and strengthening MSME market identity. Creative design shapes initial perceptions, while visual branding builds a consistent narrative and differentiates businesses. Leveraging digital platforms, the synergy between design creativity and visual coherence expands exposure, stimulates interaction, and builds emotional connections. Literature analysis indicates MSMEs strategically integrating these elements are better positioned for visibility, customer loyalty, and a strengthened competitive position. This study contributes to existing scholarship by offering a comprehensive analysis of the synergistic integration of creative design and visual branding as a strategic innovation for MSMEs, a dimension often underexplored in favor of individual components or broader digital strategies. The research emphasizes design-based innovation as vital for MSME sustainability. The implications are twofold: theoretically, it enriches literature by highlighting the critical role of visual integration; practically, it provides a vital guide for MSMEs to reframe visual branding as a strategic investment, ultimately enhancing competitiveness and fostering sustainable consumer loyalty.